A method of measuring tool tip vibration in turning operations. Issue 5 (July 2016) - Liu, Hongqi; Tang, Shengbing; He, Songping; Li, Bin; Mao, Xinyong; Peng, Fangyu
Abstract The tool tip vibration measurement has a great significance for online surface topography prediction and active vibration control. Many measurement methods have been developed. However, most of these methods are difficult to be applied in actual machining process for the following problems: the chips and cutting fluid will cause damage to the sensor or distort its measurement results and the sensor must be installed again when replacing the cutting tool. In order to overcome the above problems, this paper proposes an indirect measurement method: the vibration of the tool tip is obtained from the vibration of the measurement point on the turret. The relationship between the tool tip vibration and the turret measurement point vibration is obtained through impact tests. The vibration of the measurement point on the turret is measured via an accelerometer, which is easy to install. The measurement point is so far away from the cutting area and chip evacuation zone that the accelerometer and its measurement results will not be affected by the chips and cutting fluid. The accuracy of the measurement method is checked by comparing the calculated tool tip vibration calculated from the vibration of the turret measurement point to the directly measured results, which is measured via an accelerometer installed below the tool tip. The comparison results show that the calculated tool tip vibration at main frequencies as well as low frequencies has a high accuracy. Moreover, the effectiveness of the measurement method is verified through machined surface profile.